Stroke and Bleeding Risk Associated With Antithrombotic Therapy for Patients With Nonvalvular Atrial Fibrillation in Clinical Practice. Issue 7 (17th July 2015) - An, JaeJin; Niu, Fang; Lang, Daniel T.; Jazdzewski, Kristin P.; Le, Paul T.; Rashid, Nazia; Meissner, Brian; Mendes, Robert; Dills, Diana G.; Aranda, Gustavus; Bruno, Amanda
Abstract : Background: The quality of antithrombotic therapy for patients with nonvalvular atrial fibrillation during routine medical care is often suboptimal. Evidence linking stroke and bleeding risk with antithrombotic treatment is limited. The purpose of this study was to evaluate the associations between antithrombotic treatment episodes and outcomes. Methods and Results: A retrospective longitudinal observational cohort study was conducted using patients newly diagnosed with nonvalvular atrial fibrillation with 1 or more stroke risk factors (CHADS2 ≥1) in Kaiser Permanente Southern California between January 1, 2006 and December 31, 2011. A total of 1782 stroke and systemic embolism (SE) and 3528 major bleed events were identified from 23 297 patients during the 60 021 person‐years of follow‐up. The lowest stroke/SE rates and major bleed rates were observed in warfarin time in therapeutic range (TTR) ≥55% episodes (stroke/SE: 0.87 [0.71 to 1.04]; major bleed: 4.91 [4.53 to 5.28] per 100 person‐years), which was similar to the bleed rate in aspirin episodes (4.95 [4.58 to 5.32] per 100 person‐years). The warfarin TTR ≥55% episodes were associated with a 77% lower risk of stroke/SE (relative risk=0.23 [0.18 to 0.28]) compared to never on therapy; and the warfarin TTR <55% and on‐aspirin episodes were associated with a 20% lower and with a 26% lower risk of stroke/SE compared to never on therapy, respectively. The warfarin TTR <55% episodes were associated with nearly double the risk of a major bleed compared to never on therapy (relative risk=1.93 [1.74 to 2.14]). Conclusions: Continuation of antithrombotic therapy as well as maintaining an adequate level of TTR is beneficial to prevent strokes while minimizing bleeding events.